Genetic Mixed‐Stock Analysis of American Shad in Two Atlantic Coast Fisheries: Delaware Bay, USA, and Inner Bay of Fundy, Canada. (19th November 2014) - Waldman, John; Hasselman, Daniel; Bentzen, Paul; Dadswell, Michael; Maceda, Lorraine; Wirgin, Isaac
Abstract: American Shad Alosa sapidissima in the Hudson River, New York, and coastwide have shown major long‐term declines.  A possible contributing factor is commercial fisheries that harvest this population outside of the Hudson River estuary.  Using previously published and new reference microsatellite data from 33 baseline populations, our goals were (1) to estimate the proportion of Hudson River American Shad contributing to the two remaining major mixed‐stock fisheries along the Atlantic coast in Delaware Bay and the Bay of Fundy and (2) to estimate the proportions of other American Shad stocks contributing to these two fisheries at the highest level of stock specificity. Stock composition estimates for 2009 and 2010 Delaware Bay collections were made using three models that ranged from the most simple question (Hudson River and Delaware Bay populations) to one with all 33 baseline populations included.   In all cases, a Hudson River contribution nearly equal to that of the Delaware Bay contribution was observed, indicating a substantial take on the otherwise protected Hudson River population.  When all baseline populations were included for the larger 2010 Delaware Bay collection, 19 showed nonzero contributions, largely drawn from mid‐Atlantic U.S. rivers.  The 2009 Bay of Fundy collection showed contributions from across most of the species' range but was dominated by northern populations.  Mixed‐stock analyses of collections from the two sites together indicate that these estuarine fisheries harvested not only proximal populations but those originating from a wide latitudinal range. Received April 3, 2014; accepted August 5, 2014